Effects of Adverse Childhood Experiences on Female Sexual Quality of Life [22M]. (May 2018) - Mae Delara, Rykoff Ritchie; Cottrell, Connie; Savitski, Jennifer
Abstract : INTRODUCTION: Sexual quality of life serves a prominent role in overall patient health and well-being. Adverse childhood events have been shown to not only factor into the development of chronic disease such as ischemic heart disease and cancer but to also negatively impact sexual health. Our study sought to determine the association between reported adverse childhood experiences and female sexual quality of life. METHODS: This is a cross-sectional survey study that included 100 women seeking care at a Cleveland Clinic Akron General obstetrical and/or gynecologic office in Akron, Ohio. Two validated surveys, Adverse Childhood Experiences (ACE) and Sexual Quality of Life-Female (SQOL-F), were distributed to women age 18 and older. SQOL-F questionnaire items were organized into four sub-scales: psychosexual feelings, sexual and relationship satisfaction, self-worthlessness, and sexual repression. Spearman's rank correlation was employed to determine the relationship between ACE scores and overall sexual quality of life and the four SQOL-F sub-scales. RESULTS: There was no significant correlation between ACE score and overall sexual quality of life. An increasing ACE score was significantly correlated to feelings of self-worthlessness and poor psychosexual feelings (p = 0.01). CONCLUSION: Data indicated that adverse childhood experiences do not play a role in the overall sexual quality of life for women however instead may influence self-confidence and personal perceptions towards sexual experiences. Primary care physicians should consider screening for adverse childhood experiences and possibly suggesting psychological interventions to improve patient perception of self and in turn improve sexual quality of life.